PSIKOLOGI SOSIAL DALAM BIDANG LINGKUNGAN DAN BENCANA - Adelia Citra; Putri Fairuz Hidayat, Caroline Maryam Wijaya, Sulistiasih (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Natural disasters not only cause material and ecological damage, but also have serious psychological impacts on individuals and communities. The increasing frequency of disasters due to climate change is a global threat that requires a deeper understanding of human response and adaptation to disasters. Social psychology plays an important role in understanding the dynamics of human behavior, risk perception, and factors that influence disaster preparedness and response. In Indonesia, which often experiences various natural disasters, research in the field of social psychology is very important. This study aims to identify the psychological impact of disasters, assess the effectiveness of existing interventions, and develop strategies to support affected communities. The research uses an interdisciplinary approach combining theories and methods from social psychology, environmental science, and disaster management, which provides insights into social dynamics before, during, and after disasters The research shows that vulnerable communities must be better prepared in the face of disaster threats. Disaster management should include psychosocial support, community interventions and specialized approaches for vulnerable groups. Social psychologists can help communities understand information about threats and encourage appropriate behavior through effective and sustainable interventions. Natural disasters are environmentally and socio-economically destructive phenomena. To minimize their impact, communities must improve preparedness. Research in the field of social psychology can help develop better strategies to deal with disasters, restore the physical, mental and social conditions of victims, and increase community resilience in the face of future disasters.